2010
DOI: 10.1111/j.1467-9922.2010.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult Language Learning After Minimal Exposure to an Unknown Natural Language

Abstract: Despite the literature on the role of input in adult second-language (L2) acquisition and on artificial and statistical language learning, surprisingly little is known about how adults break into a new language in the wild. This article reports on a series of behavioral and neuroimaging studies that examine what linguistic information adults can extract from naturalistic but controlled audiovisual input in an unknown and typologically distant L2 after minimal exposure (7-14 min) without instruction or training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 66 publications
5
80
0
1
Order By: Relevance
“…Through the means of an interactive word learning task, it examined whether gesture can facilitate these processes, complementing the findings of other studies of gesture in early L2 learning (Gullberg et al, 2010;Kelly et al, 2009;Sueyoshi & Hardison, 2005;Tellier, 2008). This work also represents the first experimental study to directly compare how gesture enactment and gesture viewing affect L2 word learning and recall.…”
Section: Discussionmentioning
confidence: 97%
“…Through the means of an interactive word learning task, it examined whether gesture can facilitate these processes, complementing the findings of other studies of gesture in early L2 learning (Gullberg et al, 2010;Kelly et al, 2009;Sueyoshi & Hardison, 2005;Tellier, 2008). This work also represents the first experimental study to directly compare how gesture enactment and gesture viewing affect L2 word learning and recall.…”
Section: Discussionmentioning
confidence: 97%
“…The stimuli used both by Pelucchi et al and Kittleson et al were more complex than those used in typical artificial language studies. Others have used a natural language (Mandarin) presented in the context of visual information (a video clip) that contained multiple cues to word units and their meanings (Gullberg, Roberts, Dimroth, Veroude, & Indefrey, 2010). These studies indicate that learners can use co-occurrence information, with or without additional visual cues, to segment words from running speech in a variety of natural languages.…”
Section: Introductionmentioning
confidence: 99%
“…This claim has been supported by a series of studies that convincingly show that learners are capable of analysing the form of target structures at the very onset of their L2 learning. Gullberg et al (2010) exposed Dutch speakers to naturalistic but controlled weather reports in Mandarin and tested their capacity to identify target words based on minimal exposure to a typologically distant L2. Results showed that learners succeeded in recognising target words, especially disyllabic over monosyllabic words.…”
Section: Input Processing At First Exposure To An L2mentioning
confidence: 99%
“…Learners often use L1 phonology to segment the target language (e.g. Gullberg et al, 2010), and in production they often substitute L2 sounds with elements from their own phonological repertoire (Carroll, 2013;Flege, 1992). A question that remains widely unexplored is how L2 learners of a sign language cope with the task of discriminating the relevant linguistic elements from a continuous visual signal when the L1 cannot be recruited as an aid.…”
Section: Introductionmentioning
confidence: 99%